Keterkaitan Kebenaran Ilmiah, Kebenaran Filsafat, Religious Terhadap Kelestarian dan Tetap Tegaknya Negara Kesatuan Republik Indonesia. - Andriyana, Hendra; Talkah, Abu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
The integrity of the Unitary State of the Republic of Indonesia (NKRI) is a great mandate that must be preserved through the integration of scientific truth, philosophy, and religion as the main pillars in building a sovereign, just, and dignified nation. Scientific truth plays a role in providing rational foundations, empirical data, and practical solutions to address global issues such as climate change, food security, energy, and public health, while philosophy serves as an ethical guide that ensures national policies remain aligned with the values of justice, freedom, and unity as reflected in Pancasila. On the other hand, religious truth provides spiritual and moral foundations that maintain harmony in religious diversity while preventing the threats of radicalism, extremism, and national disintegration. In the context of Indonesia’s plurality, which encompasses diverse cultures, ethnicities, languages, and beliefs, the synergy between science, philosophy, and religion becomes the key to creating social harmony, strengthening solidarity, and managing diversity as a source of national strength rather than a threat. This study also emphasizes the importance of inclusive education, interdisciplinary dialogue, and religious moderation as strategies to reinforce social cohesion, increase national competitiveness, and ensure sustainable development. With this holistic approach, NKRI has a solid foundation to face the dynamics of globalization without losing its identity and national character. Therefore, safeguarding NKRI is not only about protecting territorial boundaries but also about nurturing the nation’s social integrity, morality, and spirituality so that it remains an inclusive, tolerant, advanced, and harmonious state.